The inverse is simply f(x)^-1 = 6/5x-2.
Commutative property of addition states that x + y = y + x, or in this case 83 + 6 = 6 + 83
The Nth term of the sequence is
T(n) = 2 + 4n or <em>2 (2n + 1)</em> .
Equation of a parabola is written in the form of f(x)=ax²+bx+c.
The equation passes through points (4,0), (1.2,0) and (0,12), therefore;
replacing the points in the equation y = ax² +bx+c
we get 0 = a(4)²+b(4) +c for (4,0)
0 = a (1.2)²+ b(1.2) +c for (1.2,0)
12 = a(0)² +b(0) +c for (0,12)
simplifying the equations we get
16a + 4b + c = 0
1.44a +1.2b + c = 0
+c = 12
thus the first two equations will be
16a + 4b = -12
1.44 a + 1.2b = -12 solving simultaneously
the value of a = 5/2 and b =-13
Thus, the equation of the parabola will be given by;
y= 5/2x² - 13x + 12 or y = 2.5x² - 13x + 12